The digital public domain : foundations for an open culture - Dulong de Rosnay, Mélanie; De Martin, Juan Carlos (Digital humanities series ;, 2012)
Foreword by Charles Nesson -- Introduction by Melanie Dulong de Rosnay and Juan Carlos De Martin -- Manifesto and policy recommendations -- I. Introducing the digital public domain -- 1. Communia and the European public domain project : a politics of the public domain / Giancarlo Frosio -- II. Legal framework -- 2. Consume and share : making copyright fit for the digital agenda / Marco Ricolfi -- 3. Evaluating Directive 2001/29/EC in the light of the digital public domain / Lucie Guibault -- 4. Building digital commons through open access management of copyright-related rights / Giuseppe Mazziotti -- -- III. Developments and case studies -- 5. Contractually-constructed research commons : a critical economic appraisal / Enrico Bertacchini -- 6. Social motivations and incentives in ex situ conservation of microbial genetic resources / Tom Dedeurwaerdere, Per M. Stromberg and Unai Pascual -- 7. Open knowledge : promises and challenges / Rufus Pollock and Jo Walsh -- 8. Science commons : building the research web / Kaitlin Thaney -- 9. The DRIVER project : the socio-economic benefits of a European scientific commons / Karen Van Godtsenhoven -- 10. CC Rel : the creative commons rights expression language / Hal Abelson, Ben Adida, Mike Linksvayer and Nathan Yergler -- 11. The value of registering creative works / Rolan Alton-Scheidl, Joe Benso and Martin Springer -- Select bibliography of resources cited.